The 28Si(d, α) reaction. (July 2016) - Araujo-Escalona, V; Acosta, L; Andrade, E; Barrón-Palos, L; Cantó, C; Favela, F; Huerta, A; Ortiz, M E; Solís, C; Chávez, E
Abstract: Recent techniques and experimental methods open up new ways to explore nuclear reactions relevant to nucleosynthesis at stellar combustion temperatures. In this work we focus on the case of 26 Al, isotope associated with the identification of active nucleosynthesis spots in the cosmos. Its presence in the solar system was unexpected until it was found in the Allende meteorite. It is now understood that cosmic rays induce nuclear reactions to produce 26 Al. On Earth, this process is well known and is the basis of many environmental studies. So 26 Al is not just the product of some high-metallicity star collapse. Natural Silicon targets were irradiated with deuteron beams of energies between 0.9 and 2.6 MeV. The produced 26 Al were counted later-on in an AMS facility. In this paper, we describe in detail the experimental protocol developed to quantify the number of deuterons hitting the target, as a first step to determine the total cross section.